Krökningsmätning av produktionsborrhål i MUJ - Eklundh, Henrik; Ferm, Simon (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2017)
While drilling holes it is extremely important that the drill holes are drilled as straight as possible. Even with the advances in drilling technology over the years it is still almost impossible. This is especially the case as the drilling depth increases. Drill hole deviation is affected by a variety of factors including drilling techniques such as weight on bit (WOB) or drill string diameter and rock properties such as density and crystal structure. It is important to study the deviation of the drill holes to ensure that the borehole is aligned correctly. When there is deviation within a boreholes major negative consequences can occur. This thesis describes the results from deviation measurements of drill holes from two different drifts within the ore body ”Alliansen” in the LKAB mine in Malmberget (MUJ). In the first drift, the production holes were drilled with a 115 mm drill bit, and in the second a drill bit of 105 mm. This is based on a project “Klenare borrhål” initiated by LKAB Wassara, a subsidiary of LKAB. LKAB Wassara wished to evaluate a possible reduction of drill hole diameter from the current 115 mm, to 105 mm. If the project had positive outcome, further attempts with an even smaller borehole diameter of 89 mm would be tested. There will also be curvature measurements as part of the evaluation of Wassaras new drill hammer, W90. The results of the measurements show that the average deviation of drill holes drilled with a larger diameter drill bit had much higher deviation than for the smaller diameter drill holes drilled with a smaller drill bit.